A modified electrode and detection method for detecting manganese (II) ions in water environment

Through the use of NIFE2O4 NPS and CEO2 NPS in the water environment, laser -graphene electrodes modified by CEO2 NPS solve the problem of insufficient sensitivity and high cost of manganese (II) ion detection in existing technologies, and achieve efficient and convenient water environment manganese (II ) Ion detection.

CN118443752BActive Publication Date: 2025-01-24CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410560866.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-08
Publication Date
2025-01-24
Estimated Expiration
2044-05-08

AI Technical Summary

Technical Problem

The prior art has problems such as insufficient sensitivity, high cost and complex equipment in the detection of manganese (II) ion in water environments, making it difficult to achieve fast, convenient and efficient detection.

Method used

A laser-induced graphene electrode modified based on NiFe2O4 NPs and CeO2 NPs was used to prepare an integrated composite three-electrode through laser-induced etching technology to improve the sensitivity and detection efficiency of the electrode.

Benefits of technology

It achieves rapid and accurate detection of manganese (II) ions in the water environment, has a lower detection limit and a wide linear detection range, and has low equipment manufacturing cost, making it suitable for mass production and on-site monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118443752B_ABST
    Figure CN118443752B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified electrode and a detection method for detecting manganese (II) ions in a water environment, and belongs to the technical field of water quality detection. The present invention modifies a laser-induced graphene electrode by NiFe2O4NFs and CeO2 for the first time, thereby preparing an integrated graphene electrode NiFe2O4 / CeO2 / LIG; the present invention upgrades the traditional three-electrode system, adopts an integrated composite LIG electrode, and the integrated laser-induced graphene electrode prepared with a polyimide film as a substrate has a lower production cost, can be mass-produced, and the integrated electrode has good flexibility; the surface area of ​​the modified electrode is increased, the number of active sites for the reaction is increased, the conductivity is enhanced, and the hydrophilicity is also improved. When the concentration of manganese (II) ions is detected by an electrochemical method, the current response is significantly improved; in addition, the NiFe2O4 / CeO2 / LIG prepared by the present invention has a wide linear range, and has better reproducibility and stability, which provides more possibilities for detecting manganese (II) ions in actual water environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water body detection, and in particular to a modified electrode for detecting manganese (II) ions in a water environment and a detection method. Background Art

[0002] In recent years, electrochemical sensors are developing towards portability, miniaturization, intelligence and integration. Electrochemical sensors composed of a flexible composite three-electrode system and an electrochemical workstation have gradually become a focus of current research.

[0003] As one of the most active rare earth metal oxides, CeO2 has attracted widespread attention and has been widely used in catalysts, solid fuel cells, sensors and other fields. CeO2 material is a cubic fluorite structure. 2- Located at the center of the tetrahedron composed of Ce sublattice, Ce 4+ They are closely arranged in a face-centered cubic structure, with each Ce atom coordinated with 8 O atoms, and each O atom coordinated with 4 Ce atoms. Depending on the oxygen content in the external environment, CeO2 can be converted into Ce2O3 or CeO2. This special crystal structure makes it very easy for oxygen vacancy defects to appear in the CeO2 lattice, which makes the CeO2 material have better catalytic performance. ] CeO2 also has high redox ability and high oxygen mobility. 4+ / Ce 3+ Rapid conversion ability, therefore, is widely used as an active carrier or active catalytic substance. On the other hand, CeO2, as a transition metal oxide, is low in price, has high thermal stability, and excellent catalytic oxidation ability, making it an ideal substitute for precious metal catalysts.

[0004] Based on the above content, the present invention proposes a manganese (II) ion detection method based on a composite material modified electrode and a device-based sensor matched therewith, which can more conveniently and quickly complete the determination of manganese (II) ions in a water environment. Summary of the invention

[0005] The purpose of the present invention is to provide a method for detecting manganese (II) ions in an aqueous environment based on a composite material modified electrode and a device design and application in the sensor preparation process, to prepare an integrated graphene electrode NiFe2O4 / CeO2 / LIG modified by NiFe2O4 NPs (nanoparticles) and CeO2 NPs (nanoparticles), to prepare a corresponding integrated sensor using the modified integrated composite electrode, and to successfully apply it to the detection of manganese (II) ions in an aqueous environment.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A modified electrode for detecting manganese (II) ions in an aqueous environment is composed of laser-induced graphene and NiFe2O4 / CeO2 modified on the surface of the graphene.

[0008] Preferably, the modified electrode preparation method is as follows:

[0009] A1. Using polyimide film as a flexible substrate, laser-induced etching technology was used to prepare an integrated composite three-electrode. The circular area in the middle of the integrated electrode was the working electrode, and the areas on both sides were the counter electrode and the reference electrode, respectively. All three electrodes were graphene electrodes.

[0010] A2, dissolving and dispersing NiFe2O4 NPs (nanoparticles) and CeO2 NPs (nanoparticles) using deionized water and Nafion dispersion liquid;

[0011] A3. Apply the dispersed liquid droplets prepared in A2 to the working electrode of the integrated composite three-electrode described in A1 to obtain an integrated graphene electrode NiFe2O4 / CeO2 / LIG modified with NiFe2O4 NPs (nanoparticles) and CeO2 NPs (nanoparticles).

[0012] Preferably, the ratio of the NiFe2O4 nanoparticles to the CeO2 nanoparticles in A2 is 1:4 to 4:1.

[0013] A method for detecting manganese (II) ions in a water environment, specifically comprising the following steps:

[0014] S1. Using polyimide film as a flexible substrate, laser-induced etching technology was used to prepare an integrated composite three-electrode. The circular area in the middle of the integrated electrode was the working electrode, and the areas on both sides were the counter electrode and the reference electrode, respectively. All three electrodes were graphene electrodes.

[0015] S2, preparing an integrated graphene electrode NiFe2O4 / CeO2 / LIG modified by NiFe2O4 NPs (nanoparticles) and CeO2 NPs (nanoparticles);

[0016] S3, using the NiFe2O4 / CeO2 / LIG prepared in S2 as a working electrode to prepare a NiFe2O4 / CeO2 / LIG sensor;

[0017] S4. Using the NiFe2O4 / CeO2 / LIG sensor prepared in S3, the manganese (II) ions in the water body to be tested are measured.

[0018] Compared with the prior art, the present invention provides a modified electrode and a detection method for detecting manganese (II) ions in an aqueous environment, which have the following beneficial effects:

[0019] (1) The present invention upgrades the traditional three-electrode system and adopts an integrated composite LIG electrode. All three electrodes are laser-induced graphene. The sensitivity of the electrode is improved by dripping a mixed modification solution of NiFe2O4NPs and CeO2NPs on the working electrode, and an integrated NiFe2O4 / CeO2 / LIG electrode is successfully prepared. Compared with the traditional three-electrode system (LIG electrode, Pt wire counter electrode, Ag / AgCl reference electrode), the integrated laser-induced graphene electrode prepared with polyimide film as the substrate has lower production cost and can be mass-produced. In addition, the integrated electrode has good flexibility and can be bent to a certain extent during use. It has a wider application range in the actual detection process and is simpler and more convenient.

[0020] (2) The present invention proves that the composite electrode can improve the electrochemical detection effect through analysis methods such as SEM, EDS mapping, contact angle, and electrochemical active area. At the same time, CV and EIS electrochemical characterization methods are used to prove that the integrated NiFe2O4 / CeO2 / LIG electrode has high electron transfer ability and point catalytic activity. Under the optimal detection conditions, the integrated NiFe2O4 / CeO2 / LIG electrode is used to detect Mn(Ⅱ) ion solutions of different concentrations, and the detection range of the electrode is 8μg / L~2mg / L. The minimum detection limit is 1.72μg / L after theoretical calculation. Compared with the prior art, the integrated electrode prepared by the present invention has the lowest detection limit in the electrochemical detection process and has a wider linear detection range. At the same time, the present invention experimentally detects the anti-interference, reproducibility and stability of the integrated NiFe2O4 / CeO2 / LIG electrode. The modified composite electrode detected the RSD of divalent manganese test solution containing different concentrations of interfering ions <, the electrode has good reproducibility, the relative standard deviation (RSD) of the peak current of the five electrodes is 3.1%, and the peak current drops to 80.3% of the original after the electrode is placed for 15 days, and the electrode has good stability. The recovery rate of tap water and groundwater samples was tested by the spiked experiment method, and the recovery rate was within an acceptable range, indicating that the NiFe2O4 / CeO2 / LIG electrode can be used for actual water sample detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the preparation and detection of the NiFe2O4 / CeO2 / LIG electrode mentioned in Example 1 of the present invention;

[0022] Figure 2 This is a SEM characterization image of the LIG electrode interface before and after modification mentioned in Example 1 of the present invention, wherein: Figure 2 (A) shows the SEM characterization image of the bare LIG electrode. Figure 2(B) shows the LIG electrode modified with NiFe2O4 NPs and CeO2 NPs.

[0023] Figure 3 This is an EDS mapping characterization diagram of the surface of the NiFe2O4 / CeO2 / LIG electrode prepared in Example 1 of the present invention, wherein: Figure 3 (A) is the overall spectrum of the electrode surface scan, Figure 3 (B) is the proportion of each element in the scan area. Figure 3 (C), (D), and (E) are the scans of each Fe, Ni, and Ce element, respectively;

[0024] Figure 4 It is a contact angle characterization diagram of the bare LIG electrode, NiFe2O4 / LIG electrode and NiFe2O4 / CeO2 / LIG electrode mentioned in Example 1 of the present invention;

[0025] Figure 5 : EIS graphs of the bare LIG electrode, the NiFe2O4 / LIG electrode and the NiFe2O4 / CeO2 / LIG electrode mentioned in Example 1 of the present invention;

[0026] Figure 6 This is a schematic diagram of the experimental results mentioned in Example 1 of the present invention, wherein: Figure 6 (A)-(C) are CV graphs of bare LIG electrode, NiFe2O4 / LIG electrode and NiFe2O4 / CeO2 / LIG at different scan rates, respectively;

[0027] Figure 7 This is a schematic diagram of the results of detecting Mn(II) using the SWCSV method using different electrodes mentioned in Example 1 of the present invention;

[0028] Figure 8 This is a schematic diagram of the experimental condition optimization results mentioned in Example 1 of the present invention, wherein: Figure 8 (A) and (B) are the optimization of the concentration ratio of NiFe2O4 NPs and CeO2 NPs, respectively. Figure 8 (C) and (D) are the optimization of deposition time;

[0029] Fig. 9 It is a relationship diagram of different concentrations of Mn (II) and the SWCSV curve of the dissolution peak mentioned in Example 1 of the present invention;

[0030] Fig.10 This is a schematic diagram of the interference of coexisting ions in the test solution mentioned in Example 1 of the present invention, wherein: Fig.10 (A) is the reproducibility test of the electrode, Fig.10 (B) is the detection of electrode stability;

[0031] Fig.11 Schematic diagram of the repeatability and stability test results mentioned in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0033] It should be emphasized that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods, devices and materials similar or equivalent to those herein can be used in the practice or testing of the present invention, preferred methods, devices and materials are now described.

[0034] The present invention proposes a modified electrode for detecting manganese (II) ions in an aqueous environment, namely an integrated NiFe2O4 / CeO2 / LIG electrode, and also proposes a method for detecting manganese (II) ions in an aqueous environment using the electrode. The specific embodiments are as follows.

[0035] Embodiment 1:

[0036] A method for detecting manganese (II) ions in a water environment, specifically comprising the following steps:

[0037] (1) Electrode pretreatment: Cut the prepared whole plate electrode into the required individual electrodes, apply film and silver paste to the individual electrodes one by one, and use infrared lamp to dry them for later use. Disperse NiFe2O4 NPs and CeO2 NPs in 8 ml of deionized water and 2 ml of Nafion mixed dispersion in a concentration range of 1:4 to 4:1, and then dissolve and disperse them in 2 to 4 ml of Nafion mixed dispersion. μ The prepared dispersed liquid droplets of L were applied to the working electrode of the integrated electrode to prepare an integrated graphene electrode NiFe2O4 / CeO2 / LIG modified based on NiFe2O4 NPs and CeO2 NPs, and the modified integrated electrode was baked and set aside.

[0038] (2) Electrochemical detection: The modified integrated electrode is connected to an electrochemical workstation for electrochemical detection. The working electrode reacts with the substance to be detected to generate a sensing signal, which is then converted into a recognizable electrical signal proportional to the concentration of the target substance by the electrochemical workstation and displayed on a computer, thereby achieving qualitative or quantitative analysis and detection of the target substance. The preparation and detection process is as follows: Figure 1 The specific contents are as follows:

[0039] 2.1) Material characterization

[0040] SEM characterization

[0041] SEM scans the surface of a sample by focusing an electron beam to produce an image of the sample surface, which can intuitively show the morphology, size and distribution of the sample. Figure 2 As shown in the figure, it can be seen that the surface of the modified LIG electrode has undergone obvious changes.

[0042] See also Figure 2 (A) SEM image of bare LIG electrode Figure 2 As shown in (A), the electrode surface has a layered porous structure with obvious wrinkles. Figure 2 (B) is a LIG electrode modified with NiFe2O4 NPs and CeO2 NPs. Figure 2 (B) It can be seen that the dot-shaped nanoparticles are dispersed on the graphene surface. The presence of these nanoparticles changes the roughness of the electrode, thereby increasing the active specific surface area of ​​the electrode. At the same time, both nanoscale modifiers have strong electrocatalytic ability. After being successfully modified on the electrode surface, the catalytic ability and adsorption performance of the electrode can be further improved.

[0043] EDS mapping characterization

[0044] EDS mapping refers to the surface distribution diagram of the energy spectrum, which is used to provide information on the distribution of elements in the sample. The EDS mapping characterization diagram of the prepared NiFe2O4 / CeO2 / LIG electrode surface is shown in Figure 3 shown.

[0045] See also Figure 3 , Figure 3 (A) is the overall spectrum of the electrode surface scan, Figure 3 (B) The figure shows the percentage of each element in the scanning area. It can be seen that the coverage of Ce, Fe, and Ni elements on the surface of NiFe2O4 / CeO2 / LIG electrode is relatively high. Figure 3(C), (D), and (E) are scanning images of each element, respectively. It can be seen from the figure that Fe and Ni elements have similar distribution states on the electrode surface, indicating that NiFe2O4 NPs are successfully modified on the electrode surface. The distribution state of Ce element is different from that of Ni and Fe elements, indicating that the mixing of the two modifications does not affect their respective existence states and can still play their respective catalytic effects well.

[0046] Contact angle characterization

[0047] The contact angle refers to the angle between the tangent lines of the gas, liquid and solid interfaces formed when a drop of deionized water is dropped on the solid surface. The size of the contact angle reflects the wettability of the liquid to the solid, that is, the hydrophilicity of the solid surface. The change in the contact angle before and after electrode modification can indicate whether the electrode is in better contact with the solution. Therefore, the contact angle of the electrode before and after modification was characterized. The hydrophilicity of the working electrode in the integrated composite electrode (i.e., NiFe2O4 / CeO2 / LIG electrode) was tested, and the contact angle is represented by θ. The size of the contact angle is negatively correlated with the hydrophilicity. The smaller the contact angle, the better the hydrophilicity of the material. Please refer to Figure 4 , Figure 4 (A), (B), (C) are the contact angles of bare LIG electrode, NiFe2O4 / LIG electrode and NiFe2O4 / CeO2 / LIG electrode, which are 86°, 68° and 56° respectively. After adding the modifier, the hydrophilicity of the integrated electrode is gradually enhanced, which can make the working electrode adsorb more Mn(Ⅱ) ions during electrochemical detection, thereby improving the sensitivity and peak current of the electrode.

[0048] 2.2) Electrochemical performance analysis

[0049] EIS is an effective tool for evaluating the electron transfer capacity of an electrode surface in detail. The semicircle diameter of the EIS is equal to the electron transfer resistance (Ret), which depends on the insulating and dielectric properties of the electrode and electrolyte interface.

[0050] In order to evaluate the electron transfer ability of different electrode surfaces, this experiment still selected K3[Fe(CN)6] solution as a probe to perform electrochemical impedance spectroscopy on the integrated electrode before and after modification. Figure 5 The black scatter plot in the middle is the detection diagram of the bare integrated LIG electrode, the red scatter plot is the integrated LIG electrode modified with only NiFe2O4 NPs, and the circle radius is smaller than that of the bare LIG electrode. The blue scatter plot is the integrated electrode modified with a mixture of NiFe2O4 NPs and CeO2 NPs, and the circle radius is the smallest. The smaller the circle radius, the smaller the Fe(CN)6 3- / 4-The faster the electron transfer rate on the electrode surface, the smaller the resistance and the better the conductivity of the electrode. Therefore, through EIS experiments, it can be found that the integrated LIG electrode modified with a mixed solution of NiFe2O4 NPs and CeO2 NPs has the lowest resistance during electrochemical detection.

[0051] To further study the electrochemical active sites, during electrochemical detection, the area on the working electrode that actually participates in the reaction is called the electrochemical active surface area (ECSA). The calculation method for the electrochemical active surface area is as follows:

[0052] ECSA=Cdl / Cs

[0053] Here, Cdl refers to the electrochemical double-layer capacitance, which can be obtained by two methods: (1) In the potential range where the electrode itself does not undergo redox reaction, measure the double-layer capacitance current in the non-Faraday interval corresponding to the cyclic voltammetry curve at different scan rates, and calculate it after linear fitting. (2) Use electrochemical impedance spectroscopy to measure the impedance corresponding to different frequencies and calculate it. In order to detect the electrochemical active area of ​​the integrated LIG electrode, this experiment measured the double-layer capacitance current in the non-Faraday interval corresponding to the cyclic voltammetry curve at different scan rates, and performed linear fitting. The potential range was set to ensure the redox reaction of the electrode itself. The experimental results of this experiment are shown in the figure. Figure 6 As shown, Figure 6 (A), (B), (C) correspond to the cyclic voltammetry curves of LIG, NiFe2O4 / LIG and NiFe2O4 / CeO2 / LIG electrodes at 20mv / s-100mv / s, respectively. Through fitting calculation, it can be concluded that Figure 6 (D) Linear fitting diagram, from Figure 6 (D) It can be seen that the double layer capacitances of LIG, NiFe2O4 / LIG, and NiFe2O4 / CeO2 / LIG electrodes are 2.4 mF cm -2 、5.8mF cm -2 、7.4mF cm -2 The larger the double-layer capacitance of the electrode, the larger the electroactive area of ​​the electrode. Therefore, the electrochemical active area of ​​the modified electrode gradually increases, which can provide more active sites for the redox reaction of Mn(Ⅱ) ions.

[0054] The electrochemical behaviors of different modified electrodes were studied. The present invention upgraded the electrode system and adopted an integrated LIG electrode. In order to reflect the advantages of the integrated electrode, the single LIG electrode was compared with the integrated electrode under the same experimental conditions, as follows Figure 7 (A) is shown. Figure 7 As can be seen in (A), the peak positions of the integrated electrode and the individual electrode are consistent, at around 0.65V, but the peak current of the integrated electrode is much greater than that of the individual electrode. This is because laser-induced graphene is used in the integrated electrode to replace the Pt wire counter electrode and Ag / AgCl reference electrode in the traditional electrode, and graphene itself has good conductivity and excellent electron transfer ability, which makes the integrated electrode have a relatively small resistance during use. Therefore, the integrated LIG electrode was used in the process of this experiment.

[0055] Figure 7 (B) Detection of 1 mg / L Mn(Ⅱ) solution using the SWCSV method, with the electrode peak at around 0.65 V. Figure 7 The black curve in (B) is the detection curve of the bare LIG electrode, with a peak current value of 5μA. After modification with NiFe2O4 NPs, the peak current has been significantly improved to about 10.50μA, which is about 2 times higher than that of the bare electrode. After further modification with CeO2 NPs, the peak current is further improved. After the integrated LIG electrode is modified with NiFe2O4 NPs and CeO2 NPs, the peak current value is about 17μA, which is about 3.4 times higher than that of the bare electrode. Due to the good conductivity of the integrated electrode itself, transition metal oxide nanoparticles with good catalytic and adsorption properties are further modified on this basis to jointly improve the peak current in the electrochemical detection process.

[0056] In order to explore the electrochemical properties of different electrodes, K3[Fe(CN)6] was used as an electrochemical redox probe to carry out CV experiments. Figure 7 (C) is the CV experiment of LIG, NiFe2O4 / LIG, and NiFe2O4 / CeO2 / LIG electrodes. A pair of reversible redox peaks will appear in each electrode during the CV experiment. The redox peak potential difference of the unmodified integrated LIG electrode is 415mV, the oxidation peak current is 78.7μA, and the reduction peak current is 54μA. The redox peak potential difference of the NiFe2O4 / CeO2 / LIG electrode is 245mV, the oxidation peak current is 108.5μA, and the reduction peak current is 82.8μA. Compared with the bare electrode, the peak potential difference of the modified electrode decreased by 170mV, the oxidation peak current increased by 29.8μA, and the reduction peak current increased by 28.8μA. This indicates that the reversibility of the modified NiFe2O4 / CeO2 / LIG integrated electrode is significantly increased during the scanning of K3[Fe(CN)6] solution, and the increase in electron transfer rate leads to an increase in the redox peak current, indicating that the electrochemical activity of the modified electrode is enhanced during electrochemical detection.

[0057] 2.3) Optimization of experimental conditions of the present invention

[0058] In the experiment of this embodiment, the concentration ratio and deposition time of NiFe2O4 NPs and CeO2 NPs in the mixed modification solution were optimized, and the control variable method was used to perform the optimization experiment.

[0059] The concentration, morphology, and dosage distribution of the modified materials play a crucial role in the electrochemical reaction, so the concentration ratio of NiFe2O4 NPs and CeO2 NPs was first optimized. Figure 8 (A) and (B) are the optimized experimental results. When the concentration ratio of NiFe2O4 NPs and CeO2NPs increases from 1:4 to 4:1, the peak current in the electrochemical reaction process increases first and then decreases. When the ratio is 2:3, the peak current value is the largest. This is because as the ratio continues to increase, the catalytic effect of CeO2 will gradually increase, and the number of active sites on the integrated LIG electrode will increase. The peak current shows a downward trend. This may be because the excess metal oxide on the electrode surface will reduce the conductivity of the electrode. Therefore, 2:3 is selected as the best ratio. At this time, the concentrations of NiFe2O4 NPs and CeO2 NPs in the mixed modification solution are 0.4mg / mL and 0.6mg / mL, respectively.

[0060] Figure 8 (C) and (D) are the optimization of deposition time during electrochemical detection. When the deposition time increases from 150s to 350s, the peak current gradually increases. This is because as the deposition time increases, the electrode surface has enough time to adsorb Mn(Ⅱ) ions in the solution, and at the same time, the Mn(Ⅱ) ions have enough time to undergo redox reactions, so the current value will increase. However, it can be seen from Figure (D) that when the deposition time is greater than 300s, the peak current increases very slowly. In order to comprehensively consider the efficiency of the peak current response and the deposition time, 300s is selected as the optimal deposition time.

[0061] 2.4) Analysis of anti-interference, stability and reproducibility of modified electrodes

[0062] In order to apply the electrochemical sensor to the detection of actual water samples, the present invention detects other ions coexisting with Mn(II) ions in the actual water environment to observe whether these interfering ions will interfere with the detection of Mn(II) ions. The experiment of this embodiment selected some anion and cation interfering ions commonly present in the water environment for actual detection. Anions include SO4 2- 、NO3 - 、HCO3 - and Cl - etc., the selected cation is: K + 、Na + Mg2+ 、Zn 2+ , Pb 2+ and NH4 + The concentration of these interfering ions is 25 times that of the ions to be measured. After adding them, the peak current changes of Mn(Ⅱ) ions are observed and detected. The experimental results are as follows Fig. 9 shown.

[0063] In order to verify the performance of the prepared integrated NiFe2O4 / CeO2 / LIG electrode, the reproducibility and stability of the electrode were tested. Fig.10 (A) is the reproducibility test of the electrode. After calculation, it can be obtained that the relative standard deviation (RSD) of the peak current of the five electrodes is 3.1%, indicating that the integrated NiFe2O4 / CeO2 / LIG electrode has good repeatability. Fig.10 (B) is the detection of electrode stability. The same electrode was placed in the air for 5 days, 10 days and 15 days respectively. The electrodes placed for different days were used to detect the test solution containing Mn (II) ions of the same concentration. It can be seen that with the increase of the placement time, the peak current during electrode detection gradually decreases. Compared with the newly prepared modified electrode, the peak current of the electrode placed for 15 days is reduced to 80.3% of the original, indicating that the prepared integrated NiFe2O4 / CeO2 / LIG electrode has good stability.

[0064] 2.5) Detection range and detection limit of modified electrodes

[0065] The prepared Mn(Ⅱ) ion test solution was diluted with HAc-NaAc buffer solution of pH=5.5, and the test solution was diluted to different concentrations. Under the optimal experimental conditions, electrochemical detection was carried out using the modified integrated NiFe2O4 / CeO2 / LIG electrode. Fig.11 (A) and (B) are experimental results: the electrochemical sensor shows a good linear relationship in the detection of Mn(II) ions in water within the range of 8μg / L to 2mg / L. The linear regression equation is:

[0066] y=0.029x-0.304(R 2 =0.984)

[0067] This shows that the electrochemical sensor designed in this experiment has high sensitivity for the detection of Mn(Ⅱ) ions in a wide concentration range, which means that this method also has good sensitivity at low concentrations. Theoretical calculations show that when the signal-to-noise ratio S / N=3, the detection limit of the integrated NiFe2O4 / CeO2 / LIG electrode for detecting Mn(Ⅱ) ions is 1.72μg / L.

[0068] The NiO / Fe3O4 / LIG electrode constructed by the method proposed in the present invention has a lower detection limit and a larger linear range than other electrodes for detecting Mn(II) ions at present, and the comparison is shown in Table 1. At the same time, compared with other studies, the electrode prepared by the present invention has a very low production cost and good flexibility, and is more suitable for on-site monitoring.

[0069] Table 1 Comparison of detection limits and linear ranges of different methods for detecting Mn(Ⅱ) ions

[0070]

[0071] 2.5) Actual water sample testing

[0072] The ultimate goal of preparing an electrochemical sensor is to be able to be used for actual water sample detection. The experiment of this embodiment uses the spike method to evaluate the prepared integrated NiFe2O4 / CeO2 / LIG electrode. The specific operating steps of the spike method are: use laboratory tap water and simply treated groundwater to replace the HAc-NaAc buffer solution to prepare 100μg / L and 500μg / L solutions containing Mn(Ⅱ) ions. Table 2 is the experimental results. It can be seen that the recovery rate of Mn(Ⅱ) ions in tap water samples and groundwater samples is 98.60%-118.18%, and the relative standard deviation (RSD) is <8.14%. It can be seen from the experimental results that the recovery rate and relative standard deviation are within the allowable range, proving that the prepared electrochemical sensor can be used for the detection of actual water samples.

[0073] Table 2 Detection of actual water samples

[0074]

[0075]

[0076] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Mn in a water environment 2+ A modified electrode for ion detection, characterized in that: It is composed of laser-induced graphene and NiFe2O4 / CeO2 modified on its surface; The modified electrode preparation method is as follows: A1. Using polyimide film as a flexible substrate, laser-induced etching technology was used to prepare an integrated composite three-electrode. The circular area in the middle of the integrated electrode was the working electrode, and the areas on both sides were the counter electrode and the reference electrode, respectively. All three electrodes were graphene electrodes. A2, dissolving and dispersing NiFe2O4 nanoparticles and CeO2 nanoparticles using deionized water and Nafion dispersion; A3. Apply the dispersed droplets prepared in A2 to the working electrode of the integrated composite three-electrode described in A1 to obtain an integrated graphene electrode NiFe2O4 / CeO2 / LIG modified with NiFe2O4 nanoparticles and CeO2 nanoparticles.

2. Mn in a water environment according to claim 1 2+ A modified electrode for ion detection, characterized in that: The concentration ratio of the NiFe2O4 nanoparticles and the CeO2 nanoparticles in A2 is 1:4 to 4:

1.

3. A modified electrode according to any one of claims 1 to 2 is used to carry out a method for the removal of Mn in an aqueous environment. 2+ An ion detection method, characterized in that The specific steps include: S1. Using polyimide film as a flexible substrate, laser-induced etching technology was used to prepare an integrated composite three-electrode. The circular area in the middle of the integrated electrode was the working electrode, and the areas on both sides were the counter electrode and the reference electrode, respectively. All three electrodes were graphene electrodes. S2, preparing an integrated graphene electrode NiFe2O4 / CeO2 / LIG modified by NiFe2O4 nanoparticles and CeO2 nanoparticles; S3, using the NiFe2O4 / CeO2 / LIG prepared in S2 as a working electrode to prepare a NiFe2O4 / CeO2 / LIG sensor; S4. Using the NiFe2O4 / CeO2 / LIG sensor prepared in S3 to measure the Mn in the water 2+ ions were measured.

Citation Information

Patent Citations

  • Modification method of catalyst for producing hydrogen through photocatalytic water splitting

    CN107008334A

  • Graphene electrode for detecting chromium (VI) ions in water environment and application

    CN116593553A